A PVA-based oil well cement fluid loss additive and a preparation method thereof
Patent Information
- Application Number
- CN202211439547.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-11-17
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2042-11-17
AI Technical Summary
[0003]目前,该类型降失水剂社会化产品对水泥的适应性较差,不同厂家的水泥以及同一厂家不同批次的水泥,失水效果相差较大,影响固井质量稳定性;采购的社会化产品通常价格较高,成本增加
[0012] Compared with existing technologies, the PVA-based water loss reducing agent described in this invention contains a polyvinyl alcohol structure. The raw materials for its preparation are: 50-65 wt% polyvinyl alcohol, PVA17-88; 3-5 wt% crosslinking agent, borax; and the balance is 30-47 wt% filler, silica fume. When this water loss reducing agent containing the polyvinyl alcohol structure is added to cement slurry, the polyvinyl alcohol crosslinks with the borax crosslinking agent, forming a more stable network structure. This network interweaves with the cement hydrates, forming a dense, impermeable filter membrane under pressure differential, effectively controlling water loss in the cement slurry and preventing cross-contamination, thus achieving the purpose of "anti-cross-contamination." Furthermore, this invention uses silica fume as an auxiliary material. The reaction of silica with cement hydrates forms hydrated calcium silicate gel, which increases adsorption capacity, reduces the permeability of cement stone, and improves the compressive strength of cement stone without affecting the thickening time. Therefore, this water loss reducing agent has enhanced adaptability to cement. Compared with similar commercial products, the PVA-based fluid loss reducer of this invention has the characteristics of low fluid loss, good anti-channeling performance, operating temperature ≤100℃, short thickening linear transition time, high compressive strength, low dosage sensitivity, strong adaptability to cement, simple preparation and low cost, which can meet the needs of medium-temperature cementing in different regions.
Smart Images

Figure BDA0003948042860000051 
Figure BDA0003948042860000061
Abstract
Description
Technical Field
[0001] This invention belongs to the technical field of oil well cement admixtures in drilling engineering, specifically relating to a PVA-based oil well cement fluid loss reducer and its preparation method. Background Technology
[0002] With the continuous development of the Zhongyuan Oilfield, oil and gas resources are gradually being depleted. Years of injection-before-production have led to high formation water content, pressure instability, and frequent oil-gas-water channeling. The use of polyvinyl alcohol (PVA)-based fluid loss control agents in well cementing can effectively control fluid loss and plays a crucial role in protecting oil and gas reservoirs. PVA-based fluid loss control agents include polyvinyl alcohol and its crosslinked derivatives. For many years, this type of fluid loss control agent has been widely used in development wells and sidetracking wells in the Zhongyuan Block. Internationally, project teams in Sudan and Chad have also consistently used this type of fluid loss control agent, indicating a significant demand.
[0003] Currently, commercially available products of this type of fluid loss reducing agent have poor adaptability to cement. The fluid loss effect varies greatly between cements from different manufacturers and even between different batches of cement from the same manufacturer, affecting the stability of cementing quality. Commercially available products purchased are usually more expensive, increasing costs. Summary of the Invention
[0004] In view of the problems existing in the existing products, the purpose of this invention is to propose a PVA-based oil well cement fluid loss reducing agent and its preparation method. The PVA-based oil well cement fluid loss reducing agent developed in this invention has strong adaptability to cement, stable performance, and low fluid loss, which is conducive to ensuring the stability of cementing quality.
[0005] This invention provides a PVA-based oil well cement fluid loss reducer, which is made of the following components by weight percentage: 50%-65% PVA; 3%-5% borax; and the balance being 30%-47% silica fume.
[0006] In an embodiment of the present invention, the degree of polymerization of the PVA is 1700-2200, the degree of hydrolysis is 85-90%, and the fineness is 60-80 mesh.
[0007] In an embodiment of the present invention, the borax is sodium tetraborate decahydrate with a purity ≥99.0%.
[0008] In embodiments of the present invention, the silicon powder has a fineness of 500 mesh or higher, a silicon dioxide content of ≥90.0%, and a density of 2.65±0.10 g / cm³. 3 .
[0009] In an embodiment of the present invention, the PVA-based oil well cement dehydration agent is made of the following components by weight percentage: 60-65% PVA; 5% borax; 30-35% silica powder.
[0010] The present invention provides a method for preparing PVA-based oil well cement fluid loss reducing agent as described above, comprising the following steps: first adding polyvinyl alcohol (PVA) to a mixer, then adding borax, and finally adding silica powder and mixing for a stirring time of not less than 20 minutes to prepare a PVA-based oil well cement fluid loss reducing agent.
[0011] In an embodiment of the present invention, the preparation method of the PVA-based oil well cement fluid loss reducer is as follows: according to the material addition ratio, polyvinyl alcohol (PVA) and crosslinking agent borax are sequentially placed into a conical mixing device and mixed for at least 10 minutes. Then, silica powder is added and the mixture is stirred for another 20-30 minutes to prepare the PVA-based oil well cement fluid loss reducer.
[0012] Compared with existing technologies, the PVA-based water loss reducing agent described in this invention contains a polyvinyl alcohol structure. The raw materials for its preparation are: 50-65 wt% polyvinyl alcohol, PVA17-88; 3-5 wt% crosslinking agent, borax; and the balance is 30-47 wt% filler, silica fume. When this water loss reducing agent containing the polyvinyl alcohol structure is added to cement slurry, the polyvinyl alcohol crosslinks with the borax crosslinking agent, forming a more stable network structure. This network interweaves with the cement hydrates, forming a dense, impermeable filter membrane under pressure differential, effectively controlling water loss in the cement slurry and preventing cross-contamination, thus achieving the purpose of "anti-cross-contamination." Furthermore, this invention uses silica fume as an auxiliary material. The reaction of silica with cement hydrates forms hydrated calcium silicate gel, which increases adsorption capacity, reduces the permeability of cement stone, and improves the compressive strength of cement stone without affecting the thickening time. Therefore, this water loss reducing agent has enhanced adaptability to cement. Compared with similar commercial products, the PVA-based fluid loss reducer of this invention has the characteristics of low fluid loss, good anti-channeling performance, operating temperature ≤100℃, short thickening linear transition time, high compressive strength, low dosage sensitivity, strong adaptability to cement, simple preparation and low cost, which can meet the needs of medium-temperature cementing in different regions.
[0013] Furthermore, in the preparation of the PVA-based oil well cement dehydration agent in this embodiment of the invention, based on the differences in material dosage, density, fineness, etc., materials with a large amount of polyvinyl alcohol and a small specific gravity are added first, followed by crosslinking agents, and finally materials with a large amount of polyvinyl alcohol and a large specific gravity are added, resulting in a better dehydration effect. Detailed Implementation
[0014] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0015] This invention provides a PVA-based oil well cement slurry fluid loss reducing agent, which is made of the following components by weight percentage: 50-65% PVA; 3-5% borax; the balance being silica powder;
[0016] The degree of polymerization of the PVA is 1700-2200, and the degree of hydrolysis is 85-90%.
[0017] The oil well cement fluid loss reducing agent provided by this invention has the characteristics of strong adaptability to cement, stable performance, low fluid loss, and simple preparation, which helps to ensure the stability of cementing quality and reduce costs.
[0018] The PVA-based oil well cement slurry fluid loss reducer described in this invention has polyvinyl alcohol units and its cross-linked network structure. The main raw material is polyvinyl alcohol (PVA), meaning the formulation contains 50-65% PVA by mass, preferably 60-65 wt%, which yields better results. The PVA has a degree of polymerization of 1700-2200 and a degree of hydrolysis of 85-90%, such as 88%. In a specific embodiment of this invention, the PVA is in powder form, preferably with a fineness of 60-80 mesh.
[0019] Polyvinyl alcohol (PVA) is a water-soluble polymer with a large number of hydroxyl groups in its molecules, giving it many excellent properties such as film-forming ability, adhesion, miscibility, chemical resistance, and heat resistance. In oil well cement, PVA is used as a fluid loss reducer, having no adverse effects on thickening time and compressive strength, and effectively reducing cement slurry filtration loss and preventing gas channeling. Simultaneously, PVA molecules crosslink with a crosslinking agent (borax), and inorganic anionic functional groups complex with PVA molecules in alkaline aqueous solutions to form a network structure. This network structure significantly improves the cement slurry's ability to control fluid loss.
[0020] In a specific embodiment of the present invention, the crosslinking agent is borax, sodium tetraborate decahydrate, with a purity ≥99.0%, and the dosage is 3-5%. In the system of the invention, borax, as a crosslinking agent, crosslinks with polyvinyl alcohol molecules to form a network structure, which can effectively improve the film-forming and water-controlling ability of the water-reducing agent.
[0021] In an embodiment of the present invention, the filler in the PVA-based oil well cement fluid loss reducing agent is silica powder, which is composed of silicon dioxide, preferably with a fineness of 500 mesh or higher, a silica content of ≥90.0%, and a density of 2.65±0.10 g / cm³. 3 The dosage is 30-47%. In the system of this invention, the addition of silica fume to cement can increase compressive strength without adversely affecting thickening time or thickening profile. It also improves the stability of the water loss reducing agent and its compatibility with cement. In the PVA and crosslinking agent formulations of this invention, the stability of the water loss reducing agent is guaranteed, a feature not reported in currently available domestic or international technologies.
[0022] The above-mentioned PVA-based oil well cement fluid loss reducer is made from the following components by weight percentage: 60% PVA; 5% borax; 35% silica fume; or: 65% PVA; 5% borax; 30% silica fume.
[0023] In the example, the polyvinyl alcohol (PVA) has a degree of polymerization of 1700-2200, a degree of alcoholysis of 88%, and a fineness of 60 mesh. Commercially available products can be used, such as PVA17-88 produced by Chongqing Hualiweisheng Oilfield Chemical Technology Co., Ltd. The crosslinking agent, borax, is borax decahydrate; commercially available products such as borax from Zhengzhou Zhongtian Hongda Chemical Technology Co., Ltd. can also be used. The filler is silica powder with a fineness of 500 mesh or higher; commercially available products such as those from Puyang Hesheng Materials Co., Ltd. are also acceptable. This invention is not limited to the manufacturers listed above; any manufacturer meeting the requirements is acceptable.
[0024] Another objective of this invention is to provide a method for preparing the PVA-based oil well cement slurry fluid loss reducing agent as described above, comprising: first adding polyvinyl alcohol (PVA) to a mixer, then adding borax, and finally adding silica powder and mixing for at least 20 minutes to prepare the PVA-based oil well cement fluid loss reducing agent.
[0025] The preferred preparation steps of this invention are as follows:
[0026] Based on the differences in dosage, fineness, and density of the three materials in the water loss reducing agent according to the present invention, it is preferable to first add polyvinyl alcohol (PVA) in a conical mixer (which has a large dosage, large particle size, and low density: dosage 60%-65%, fineness 60-80 mesh, density 1.27 g / cm³). 3 Then add the crosslinking agent borax (its dosage is small, and its density is low: 5% dosage, fineness 20-30 mesh, density 1.73 g / cm³). 3 Stir at room temperature for at least 10 minutes; finally add silicon powder (which is added in larger quantities, has a smaller particle size, and the highest density: 30%-35% addition, fineness of 500 mesh or higher, density 2.65±0.10 g / cm³). 3 Stir for 20-30 minutes until well mixed to produce a high-performance PVA-based oil well cement dehydration reducer.
[0027] The physicochemical properties of the water loss reducing agent in this invention embodiment include: appearance as a white powder, drying loss ≤ 5.0%, fineness with 0.315mm sieve residue ≤ 12.0%, and density 1.75-1.80 g / cm³. 3 It is soluble in water at room temperature.
[0028] In this embodiment of the invention, the prepared PVA-based admixture is used as a fluid loss reducing agent for oil well cement, with an operating temperature up to 105℃. The PVA-based sample is added to Grade G oil well cement at a standard dosage of 1.2% (by weight of cement), followed by the addition of an aldehyde-ketone polymer dispersant at 0.5% (by weight of cement). Cement slurry is prepared according to the method specified in GB10238 for oil well cement, and its performance is evaluated according to the technical requirements for fluid loss reducing agents in oil well cement (Q / SHCG33-2016). Experiments show that, compared to similar commercially available products, the PVA-based fluid loss reducing agent for oil well cement of this invention has the characteristics of low fluid loss, short thickening linear transition time, high compressive strength, and strong adaptability to cement, which can meet the needs of medium-temperature cementing and is beneficial for application.
[0029] The present invention will be further described below with reference to the embodiments, but the present invention is not limited to the following embodiments. The raw materials involved are commercially available. The polyvinyl alcohol (PVA) has a degree of polymerization of 1700-2200, a degree of hydrolysis of 88%, and a fineness of 60 mesh; PVA17-88 produced by Chongqing Hualiweisheng Oilfield Chemical Technology Co., Ltd. is selected. The crosslinking agent is borax decahydrate, and borax products from Zhengzhou Zhongtian Hongda Chemical Technology Co., Ltd. are selected. The filler, silica powder, has a fineness of 500 mesh and was purchased from Puyang Hesheng Materials Co., Ltd.
[0030] Example 1
[0031] The present invention provides a PVA-based oil well cement fluid loss reducing agent, which is made of the following components by weight percentage: 60% PVA17-88; 5% borax; 35% silica powder (500 mesh).
[0032] The preparation steps are as follows: According to the formula ratio, first put polyvinyl alcohol and crosslinking agent (borax) into a conical stirrer and stir evenly for 10 minutes. Then add 500-mesh silica powder and stir for 20 minutes to make PVA-type oil well cement dehydration reducer.
[0033] Example 2
[0034] The present invention provides a PVA-based oil well cement fluid loss reducing agent, which is made of the following components by mass percentage: 65% PVA17-88; 5% borax; 30% silica powder (500 mesh).
[0035] The preparation steps are as follows: According to the formula ratio, first put polyvinyl alcohol and crosslinking agent (borax) into a conical stirrer and stir evenly for 10 minutes. Then add 500 mesh silica powder and stir for 30 minutes to make PVA-type oil well cement dehydration reducer, code name sample 1.
[0036] Its physicochemical properties are as follows: appearance is white powder, loss on drying ≤5.0%, fineness ≤12.0% residue on 0.315mm sieve, and density 1.75-1.80g / cm³. 3It is soluble in water at room temperature.
[0037] Example 3
[0038] 1.2% (by mass of cement) of Sample 1 was added to Tongchuan Grade G oil well cement, and 0.5% (by mass of cement) of oil well cement dispersant USZ was added. Cement slurry was prepared according to GB10238-2015 standard. The performance of medium-temperature fluid loss reducing agent was evaluated according to the enterprise standard Q / SHCG 33-2016 of China Petroleum & Chemical Corporation, "Technical Requirements for Oil Well Cement Fluid Loss Reducing Agent".
[0039] A comparison sample is also provided: Purchased sample 2 (appearance: white powder, fineness: 60 mesh, density: 1.70 g / cm³). 3 (Soluble in water at room temperature). This sample was produced by Tianjin World Oilfield Technology Co., Ltd. and its performance was evaluated in the same amount as that of the above sample 1 in Tongchuan G-grade oil well cement, using the same standard. The results are shown in Table 1.
[0040] Table 1. Influence of the oil well cement fluid loss reducing agent and similar commercially available products on cement slurry performance in this invention.
[0041]
[0042]
[0043] Experimental results show that the PVA-type oil well cement dehydration agent provided by this invention has less water loss, higher compressive strength, and a shorter 40-100BC transition time compared with commercially available products, which is more beneficial for preventing formation oil, gas, and water channeling.
[0044] Example 4
[0045] Sample 1 and Sample 2 were added to Tongchuan G (01 batch), Tongchuan G (05 batch), Jiahua G, and Three Gorges G grade cement, respectively. The water loss control performance of the medium-temperature type water loss control agent in different cements was evaluated according to Q / SHCG33-2016 "Technical Requirements for Oil Well Cement Water Loss Control Agent". The results are shown in Table 2.
[0046] Table 2 Evaluation of controlled water loss performance of Samples 1 and 2 in different cements
[0047] Tongchuan G (Batch 01) 26 30 Tongchuan G (Batch 05) 28 48 Jiahua G 30 42 Three Gorges G 40 90
[0048] Experimental results show that the PVA-based oil well cement fluid loss reducer provided by this invention has stronger adaptability to different batches of cement from the same manufacturer and cement from different manufacturers.
[0049] Example 5
[0050] 1.5% (by mass of cement) of Sample 1 and Sample 2 were added to Tongchuan G cement, and 0.5% (by mass of cement) of oil well cement dispersant USZ was added to evaluate its temperature resistance. The results are shown in Table 3.
[0051] Table 3 Evaluation of the water loss control performance of Sample 1 and Sample 2 at different temperatures
[0052] 80 12 10 90 16 15 95 26 24 100 46 42 105 102 96
[0053] Experimental results show that the PVA-type oil well cement dehydration agent provided by this invention, compared with similar commercial products, can withstand temperatures up to 105℃ and up to 100℃, and can control water loss to within 50ml, which is beneficial for controlling "gas channeling" in medium and deep wells.
[0054] The embodiments described above are merely some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, those skilled in the art can make modifications and variations to the present invention without departing from the spirit and scope of the present invention, and all other embodiments obtained are within the scope of protection of this application.
Claims
1. A PVA-based oil well cement fluid loss reducer, characterized in that, It is made from the following components by weight percentage: 50%-65% polyvinyl alcohol (PVA); 3%-5% crosslinking agent, borax; the balance being 30%-47% silica powder; the degree of polymerization of the polyvinyl alcohol (PVA) is 1700-2200, the degree of hydrolysis is 85-90%, and the fineness is 60-80 mesh; the borax is sodium tetraborate decahydrate with a purity ≥99.0%; the silica powder has a fineness of ≥500 mesh and a silica content ≥90.0%.
2. The PVA-based oil well cement fluid loss reducer according to claim 1, characterized in that, The density of the silicon powder is 2.65 ± 0.10 g / cm³. 3 .
3. The PVA-based oil well cement fluid loss reducer according to any one of claims 1-2, characterized in that, The PVA-type oil well cement fluid loss reducer has an applicable temperature of ≤100℃, and the cement slurry can effectively prevent gas channeling.
4. A method for preparing a PVA-based oil well cement fluid loss reducing agent according to any one of claims 1-3, characterized in that, Includes the following steps: First, add polyvinyl alcohol (PVA) to the mixer, then add borax, and finally add silica powder. Mix and stir for at least 20 minutes to prepare a PVA-based oil well cement dehydration reducer.
5. The preparation method according to claim 4, characterized in that, The preparation method is specifically as follows: According to the material addition ratio, polyvinyl alcohol (PVA) and crosslinking agent borax are sequentially added into a conical mixer and mixed for at least 10 minutes. Then, silica powder is added and the mixture is stirred for another 20-30 minutes to produce a PVA-based oil well cement dehydration reducer.
Citation Information
Patent Citations
Thickener and super high-density cement paste based on thickener
CN103773341A
Oil well cement latex fluid loss agent and preparation method thereof
CN106085382A